Heavy Chain Constant Region Usage in Antibodies to Peptidylarginine Deiminase 4 as a Marker of Disease Subsets in Rheumatoid Arthritis. Issue 11 (29th September 2022) - Gómez‐Bañuelos, E.; Shi, J.; Wang, H.; Danila, M. I.; Bridges, S. L.; Giles, J. T.; Sims, G. P.; Andrade, F.; Darrah, E.
Abstract : Objective: The study of autoantibody isotypes in autoimmune diseases is useful for identifying clinically relevant endotypes. This study was undertaken to study the prevalence and clinical significance of different isotypes and IgG subclasses of anti–peptidylarginine deiminase 4 (anti‐PAD4) autoantibodies in individuals with rheumatoid arthritis (RA). Methods: In 196 RA subjects and 64 healthy controls, anti‐PAD4 antibody types were determined using enzyme‐linked immunosorbent assay. We investigated associations between anti‐PAD4 antibodies and clinical outcomes, and relevant features were confirmed in an independent RA cohort. Results: Anti‐PAD4 IgG1, anti‐PAD4 IgG2, anti‐PAD4 IgG3, anti‐PAD4 IgG4, anti‐PAD4 IgA, and anti‐PAD4 IgE antibodies were more frequent in RA patients than healthy controls ( P < 0.001). Anti‐PAD4 IgG1, anti‐PAD4 IgG3, and anti‐PAD4 IgE were associated with distinct clinical features. Anti‐PAD4 IgG1 was predictive of progressive radiographic joint damage (odds ratio [OR] 4.88, P = 0.005), especially in RA patients without baseline joint damage (40% versus 0%, P = 0.003) or in those negative for anti–cyclic citrullinated peptide and/or rheumatoid factor (OR 32; P = 0.009). IgG1 was also associated with higher levels of C‐reactive protein ( P = 0.006) and interleukin‐6 ( P = 0.021). RA patients with anti‐PAD4 IgG3 had higher baseline joint damage scores (median Sharp/van der Heijde score 13 versus 7, P = 0.046), while those with anti‐PAD4 IgE had higher Disease Activity Score in 28 joints (median 4.0 versus 3.5, P = 0.025), more frequent rheumatoid nodules (31% versus 16%, P = 0.025), and more frequent interstitial lung disease (ground‐glass opacification) (24% versus 9%, P = 0.014). Anti‐PAD4 IgG1 antibody associations with joint damage were corroborated in an independent RA cohort. Conclusion: Anti‐PAD4 IgG1, anti‐PAD4 IgG3, and anti‐PAD4 IgE antibodies identify discrete disease subsets in RA, suggesting that heavy chain usage drives distinct effector mechanisms of anti‐PAD4 antibodies in RA.